Knowledge, perception and the utilization of immediate postpartum family planning among pregnant and postpartum women in Ogbomoso, southwest Nigeria - Adekunle, Adebayo D.; Aworinde, Olufemi O.; Fijabiyi, Matthew O.; Muritala, Wakeel O.; Adeniran, Muibat A.; Oyedeji, Yetunde O.; Oyedeji, Oluniyi O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The postpartum period is frequently characterised by a heightened risk of unintended pregnancies and unmet contraceptive needs, and women who wish to delay or avoid subsequent pregnancies soon after childbirth often lack access to timely and effective family planning information and services. This study aimed to determine the knowledge, perception, and utilisation of immediate postpartum family planning (IPPFP) amongst pregnant and postpartum women in Ogbomosho, Oyo State. Methods: A cross-sectional, descriptive multi-stage study design was conducted in selected hospitals in Ogbomoso, southwest Nigeria. Data obtained using a self-administered structured questionnaire were analysed using IBM SPSS version 26, and the results obtained were presented in tables. The level of significance was set at 0.05. Results: The findings in this study revealed that a larger number of respondents had good knowledge of postpartum family planning (83.30%), while a smaller number (16.70%) had poor knowledge. Regarding utilisation, despite the high level of knowledge demonstrated in this study, only 43.60% of respondents had used any method of IPPFP, while 56.4% had not. Conclusions: The high level of knowledge demonstrated by the participants in this study did not translate into the uptake of postpartum contraceptives. The study emphasises the need for improved access to diverse IPPFP options to enhance utilisation.